Análise dos efeitos das taxas de câmbio, de juros e da renda mundial sobre as exportações brasileiras de mel - Oliveira, Ana Cláudia Sampaio de (2015)
The exchange rate, interest rate and world income are important variables in an economy, because in addition to mediate commercial and financial relations of a country with the rest of the world, can serve as an incentive for productive investment, generating direct impact on exports. Thus, this study proposes to test the existence of a long-term relationship and the degree of influence of these variables on the performance of exports of Brazilian honey, between 2000 and 2011. The empirical strategy was the use of a VAR model more complete model called vector error correction (VECM). The results showed that all the explanatory variables are highly relevant to explain the oscillations occurring over time in the dependent variable export of honey. As for short-term analysis demonstrated that there is some lag time for imbalances occurring in the short term will be corrected in the long run. The relevance of factors that could cause structural breaks in the model, it was found that only the shock on the exchange rate, after the uncertainties of the electoral process in Brazil in 2002, justified the inclusion of a dummy in the model analysis.